Commuting stress: consequences and implications for employee well-being - Mohd Mahudin, Nor Diana (2010)
Unlike research on environmental variables, interpersonal relationships, personal characteristics, and organizational factors, all of which have been empirically supported as the common sources of employee stress, evidence on the effects of commuting on their well-being is relatively scarce. The purpose of this study was to investigate the relationship between commuting and individual and organizational well-being among employees who commute to work using light rail transits or commuter services on a regular basis. It is predicted that employees with high commuting stress levels would report commuting for longer duration, and workers with high commuting stress levels would report higher levels of commute displeasure, physical or somatic symptoms experienced, and intention to quit but lower levels of job and life satisfactions. A passenger survey, which comprised of questions on commute duration, transportation mode, demographical data, and variables regarding overall commuting experience as well as general work and life activities, was completed by 660 employees in Kuala Lumpur, Malaysia. Preliminary correlational analyses showed that commute duration was significantly correlated with commuting stress, and the impacts of commuting stress were evident in terms of increased commute displeasures, more physical or somatic symptoms experienced, and more intention to quit. However, contrary to expectations, there were small but significant correlations found between commuting stress and job and life satisfactions. Theoretical and practical implications for understanding the overall commuting patterns as well as traveling behaviors are discussed. Some recommendations for future research are also offered.